Voice of the customer - Yang, Kai
Voice of the Customer Capture and Analysis equips Six Sigma you with the skills needed to create and deploy surveys, capture real customers need with ethnographic methods, immediately analyze the results, and coordinate and drive responsive actions. Quality expert Kai Yang explains how to utilize the statistical methods of Design for Six Sigma to identify key customer needs and assess the cost of poor quality. He then shows how to design robust products to meet those needs, optimize product life cycles, and accurately validate their findings